Migration in Business and Human Rights policy: An overview from Argentinean implementation gap - Vazquez, Agustina; Sommer, Christian (Acta Universitatis Danubius. Juridica, 2021)
Argentina is still debating whether to issue a National Action Plan on Business and Human Rights or to sign a treaty on the subject. It has signed more than 20 human rights treaties in recent decades. It has supported the United Nations Principles on Business and Human Rights from the outset, and still, there is no National Action Plan. Objectives: This work aims to analyze how different administrations faced controversy on the topic and how migrants are being protected when working in Argentina. Prior Work: As stated by Sardi and Buhmann, development is slower for migrants, even if we have already stablished that the current legal framework does not differentiate between nationals and migrants. Approach: We propose a qualitative approach, by studying a significant number of documents that evidence little political coherence. As result, we highlight that there is poor information to set a path for development in Argentina, and that Business and Human Rights seems off focus within the Argentinean priorities.